Safety Valve Maintenance Maintenance System on Equipment in the Factory - Insani, Ganang Pandu; Ujiburrahman, Ujiburrahman (CV. Rayyan Dwi Bharata, 2024)
In the industrial world, the use of instrumentation equipment is very important in the production operations process of a factory. In line with the progress and development of science and technology which is increasingly rapid at this time, humans are always trying to find or create equipment that can make work easier in a process. For this reason, the equipment must be able to produce optimal measurements or detection. A valve is a device installed in a piping system whose function is to regulate, control and direct the fluid flow rate by opening, partially closing or fully closing. A simple valve is like a household water faucet. The use of this safety valve is very important to prevent excessive pressure which will cause damage to the valve and production machines. This research aims to determine the maintenance of safety valves on equipment in factories to prevent damage. In this research, the method of direct observation was used during the testing process. The research results show that damage to the valve causes a blockage in the flow from the valve to the pipe, damage to the safety valve has many factors, one of which is rust and corrosion caused by fluid passing through the valve, and errors in setting the pressure on the valve.